2015
DOI: 10.1016/j.apmr.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Improving Motor Control in Walking: A Randomized Clinical Trial in Older Adults With Subclinical Walking Difficulty

Abstract: Objective The objective was to test the proposed mechanism of action of a task-specific motor learning intervention by examining its effect on measures of the motor control of gait. Design Single blinded randomized clinical trial. Setting University research laboratory. Participants Forty older adults 65 years of age and older, with gait speed >1.0 m/s and impaired motor skill (Figure of 8 walk time > 8 secs). Interventions The two interventions included a task-oriented motor learning and a standard ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
1
36
1
Order By: Relevance
“…For example, recent clinical trials from Brach et al and VanSwearingen et al have shown that motor skill gait training, which targets specific gait characteristics through repetitive practice of timing and coordination of gait, can improve gait speed and improve the energy cost of walking more efficiently than a standard walking and strengthening program. [2527]…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent clinical trials from Brach et al and VanSwearingen et al have shown that motor skill gait training, which targets specific gait characteristics through repetitive practice of timing and coordination of gait, can improve gait speed and improve the energy cost of walking more efficiently than a standard walking and strengthening program. [2527]…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]11 Previously, therapeutic, individually supervised exercise led by physical therapists that includes timing and coordination components has been shown to improve walking in older adults. [13][14][15][16] Therefore, timing and coordination exercises could be an important addition to community-based health promotion group exercise programs to improve walking. Based on previous research, 14,15 and with critical input from older adults and other stakeholders, the On the Move (OTM) group-based exercise program that includes timing and coordination and focuses on improving walking was developed.…”
mentioning
confidence: 99%
“…We based sample size on pilot studies,(4547) two-tailed α=0.05 tests, an attrition rate of 10% , a class size of 10 participants, intra-cluster correlation of 0.1, published methodologies and commercially available sample size and power software (PASS 2002 ® Number Cruncher Statistical Systems, Kayesville, Utah), and ability to detect clinically meaningful(48) or moderate effect sizes (Cohen’s d =0.5). (49) We estimated that 90 participants per arm would allow us, with 80% statistical power, to detect statistical significance of a difference as small as 3.1 points in LLFDI overall function change between the two interventions; 80 per arm for 3.2 points in LLFDI disability frequency; 140 per arm for 0.1 m/s in gait speed; and 40 per arm for 50m in six-minute walk distance.…”
Section: Methodsmentioning
confidence: 99%